Determinants of within-subject variation of fasting serum leptin concentrations in healthy subjects. - Widjaja, A; Levy, J; Morris, R; Frayn, K; Humphreys, S; Horn, R; von zur Mühlen, A; Turner, R; Brabant, G (2000)
The hormone leptin is considered to contribute to body weight regulation through modulation of feeding behavior and energy expenditure. The aim of the present study was 1) to assess the day-to-day within-subject variation (biovariability) of serum leptin concentrations in healthy subjects and 2) to investigate whether this variation is associated with food intake, exercise, anthropometric measurements or various metabolic covariates (insulin, C-peptide and glucagon, glucose, lactate, 3-hydroxybutyrate (3-OHB), triglycerides, non-esterified-fatty acids and glycerol). Serum leptin levels were taken daily on 12 consecutive days after an overnight fast in 12 healthy subjects with a mean (SD) age of 22.7 (1.5) yr. and a BMI of 22.8 (1.6) kg/m2. Food intake, exercise, anthropometric measurements and various metabolic covariates were also determined during this period. The overall mean of serum leptin concentration was 33.3 pmol/L with a within-subject SD range of 27-41 pmol/L and a between-subject SD range of 18-61 pmol/L. The within-subject variance of serum leptin as a proportion of total variance was 9.5%. Within-subject variation of serum leptin concentrations is small in relation to between-subject variation in healthy, normal weight subjects. This has implications for the power of interventional or prospective studies. In men, 6.7% of the variation in serum leptin concentration was associated with body weight measured on the same day (p= 0.037). In women, however, 66% of the variation was negatively associated with 3-OHB measured on both the same and the previous day (p=0.0003 and 0.002), and positively associated with triglyceride concentration measured on the previous day (p=0.0017) and insulin measured on the same day (p=0.0002). Within-subject associations in women could be due to phasic changes in unmeasured variables, possibly related to the menstrual cycle or might suggest that energy balance may exert a delayed influence on serum leptin levels, with plasma 3-OHB and triglycerides acting as markers for the state of the fat stores that regulate leptin secretion. The differences between the genders remain unexplained, however.